P-238 Giving colleagues a voice: establishing a meaningful colleague representative group. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Pugh, Sarah
Abstract : Background: In the hospice's 2016 Colleague Survey, 45% of respondents stated 'communication between colleagues and the senior team is effective'; 30% disagreed. 58% of respondents agreed 'I have confidence in the senior leadership team'; 22% disagreed. As the hospice had been progressing through significant change since mid-2015, colleague resilience and understanding of change was critical. Aim: To establish a colleague representative group to provide an opportunity for dialogue and exchange of views between the hospice leadership team and colleague representatives on issues of mutual interest. Method: Advice was sought from the local ACAS representative on how to establish a meaningful colleague representative group. Terms of reference and an agenda structure were developed. The group was named 'The Voice'. Hospice colleagues were asked to nominate representatives. Membership included eight colleague representatives, CEO and Head of HR. ACAS were commissioned to run an initial training session with the group's membership to ensure clear understanding about the purpose of the meetings. Results: Quarterly meetings take place with 'The Voice'. At each meeting, leadership and workforce issues are discussed and actions agreed. In the 2017 Colleague Survey 62% (increase of 17% from 2016) of respondents stated that communication between colleagues and the senior team is effective and 9% (reduction of 21% from 2016) disagreed. 79% (improvement of 21%) of respondents agreed that 'I have confidence in the senior leadership team' and 4% (reduction of 18%) disagreed with this statement. Conclusion: Results from Colleague Surveys showed significant improvement in views that communication between colleagues and the senior team was effective. Establishing clear terms of reference, structured agendas and demonstrating commitment to the group through the involvement of ACAS in the initial stages helped emphasise the importance placed by leadership on the views of this group.